THE ORIGIN OF THE KEMANAK by JAAP KUNST. In Bijdragm tot de Taal-, Land- en Volkenkunde, Deel 116, 2e Afl (1960). pp. 263-9, 4 plates. - Jones, A. M. (International Library of African Music, 1960)
pages: 78
Keywords: African Music